Pendidikan Ibadah dan Akhlak Melalui Kisah Teladan Nabi Muhammad SAW: Perspektif Al-Quran dan Hadits - Kurnia Utami Nursholichah; Muh. Asharif Suleman; Ushie Uswatun Hasanah; Riza Febriansyah; Anan Marliansyah (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This research aims to explore the education of worship and morals through the exemplary story of the Prophet Muhammad SAW: the perspective of the Koran and hadith. The research method used in this research is literature study review, which includes examination of theories, writings, works, and images as reference sources. Researchers make use of a variety of sources and collect data from reference articles, journals, textbooks, and literature reviews on Moral and Worship education. The collected data is then checked carefully and analyzed using the researcher's own words and interpretations. Findings The research results show that worship education in the story of the example of the Prophet Muhammad is not only prayer but also worship education regarding dhikr, zakat and fasting. Likewise with moral education, namely in the moral education that is in the story of the example of the Prophet Muhammad, it is not only about arrogant or haughty actions, but you are not allowed to say "Ah" to your parents, let alone shout at your parents, love your parents as they love us and you are not allowed to associate anything with each other. Allah because associating partners with Allah is a very big unjust act. Research implications this research provides significant benefits contribution to researchers and readers by improving it understanding of religious and moral education based on the exemplary story of the Prophet Muhammad SAW, practical insights What is the education of worship and moral education in the story of the Prophet Muhammad SAW. By exploring content of the Al-Qur'an and Hadith, this research offers educational guidance on correct worship and morals in accordance with the exemplary story of the Prophet Muhammad written in the Al-Quran.